2007
DOI: 10.2116/analsci.23.1233
|View full text |Cite
|
Sign up to set email alerts
|

Electron Spin Resonance Analysis of Superoxide Anion Radical Scavenging Activity with Spin Trapping Agent, Diphenyl-PMPO

Abstract: A given amount of oxygen is always converted into reactive oxygen species (ROS) such as superoxide anion radicals, hydrogen peroxide, or hydroxyl radicals by various enzymatic systems in the human body. The ROS are essential mechanisms against extraneous factors, but excessive amounts cause harmful effects and oxidative damages that would induce various diseases, including cancer, cardiovascular disease, and diabetes. 1,2 Therefore, the ROS scavenging capacities of antioxidative enzymes and/or natural antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…SOSA of the glycosylated myofibrillar protein after 36 h of incubation was converted into SOD equivalent activity (U/mL) based on the SOD IC 50 value (1.0 units/mL), a value of 184 U/g of protein being obtained. Shimamura et al have reported SOSA values for a commercial oolong tea drink and red wine of 640 U/mL and 169 U/mL, respectively, 34) and Moriyama et al have suggested SOSA for Delaware of 700 U/g of dry matter. 35) These data suggest that the antioxidative activity of glycosylated chicken myofibrillar protein after a 36-h Maillard reaction was comparable to these commercial beverages and fruit when the modified myofibrillar protein was utilized as whole material.…”
Section: Relationship Between the Solubility And Modified Lysinementioning
confidence: 99%
“…SOSA of the glycosylated myofibrillar protein after 36 h of incubation was converted into SOD equivalent activity (U/mL) based on the SOD IC 50 value (1.0 units/mL), a value of 184 U/g of protein being obtained. Shimamura et al have reported SOSA values for a commercial oolong tea drink and red wine of 640 U/mL and 169 U/mL, respectively, 34) and Moriyama et al have suggested SOSA for Delaware of 700 U/g of dry matter. 35) These data suggest that the antioxidative activity of glycosylated chicken myofibrillar protein after a 36-h Maillard reaction was comparable to these commercial beverages and fruit when the modified myofibrillar protein was utilized as whole material.…”
Section: Relationship Between the Solubility And Modified Lysinementioning
confidence: 99%
“…ESR settings were: center filed 3484 G; sweep width 100 G; modulation frequency 100 kHz; modulation amplitude 1.0 G; microwave power 20 mW; receiver gain 1.6 9 10 5 ; time constant 0.6 s; and sweep time 671 s [28].…”
Section: Electron Spin Resonace (Esr)mentioning
confidence: 99%
“…Superoxide anion radical (O 2 •– ), the principal type of reactive oxygen species (ROS), plays a significant role in numerous physiological and pathological processes. , It has been demonstrated that increased generation of O 2 •– reduces nitric oxide bioavailability, thus resulting in the development of endothelial dysfunction. , Accordingly, to investigate the effect of O 2 •– on physiological events and oxidative-stress-induced diseases, selective and sensitive analysis methods enabling the assessment of O 2 •– in complicated biosystems are extremely valuable. To date, present techniques for the O 2 •– determination include electron spin resonance (ESR), , chemiluminescence, and spectrophotometry . However, the instruments needed in ESR are cumbersome and expensive, the selectivity of chemiluminescence is poor, and the sensitivity of spectrophotometry is low. , …”
mentioning
confidence: 99%